(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The integration of generative artificial intelligence (GenAI) with gamification has emerged as a powerful approach to enhance English as a Foreign Language (EFL) teaching material. This article reviews recent developments (2023–2025) in AI-supported gamified materials, focusing on their design, implementation, and impact on learner outcomes such as vocabulary retention, motivation, engagement, and communicative competence. Drawing on systematic reviews and empirical studies, it examines how GenAI tools (e.g., ChatGPT, custom bots) generate adaptive content, personalized feedback, and interactive narratives, while gamification elements (quests, badges, leaderboards) sustain interest and reduce anxiety. Key findings indicate superior long-term retention from AI-generated storytelling compared to traditional gamified apps (e.g., Duolingo), with benefits in immersion, cultural relevance, and individualization. Challenges include potential biases, over-reliance on extrinsic rewards, and accessibility gaps. The article argues for principled integration that aligns with TESOL materials development theories (Tomlinson, 2023; Afitska, 2016) to create equitable, context-sensitive resources. Future directions emphasize ethical design, longitudinal studies, and teacher training to maximize AI-gamification’s potential in diverse EFL contexts.